De musa a criadora: figuras femininas nas narrativas de artista - Izabela Baptista do Lago (2022)
The present work intends to deepen the study of the artist narrative, a literary category originated in the Germanic tradition of the Künstlerroman, which emerged in the late 18th century and reached its peak in the 19th century. The intrigue and the theme of the artist narrative concern the professional and the personal conflicts encountered by the artist, which is always the protagonist, usually a painter. We propose to focus on the female figures in these narratives and to analyze their representations from an interdisciplinary and intermedial perspective, considering historical, social, cultural and aesthetic factors. To this end, based on critical and theoretical works on the representation of women in literature and, above all, on a selected literary corpus, we identified four female figures portrayed in the artist narratives: a) the model or the muse of the protagonist male artist; b) the woman represented in the works of art produced by the male artist; c) the artist's companion; d) the female artist. We analyze each of these figures individually, which were taken from the literary corpus and from selected art pieces, confronting the main aspects of these representations with the historical and cultural context of these works. We focus more closely on the study of the figure of the woman artist, and we examine how the switch from the typical protagonist of the artist narratives – the male painter – to the female artist impacts the formal and the thematic topoï of the category, since the characters present different treatment according to their gender. As a result, we verified that the artist narratives, understood as literary texts that present an intersection between fiction and historical documents, transpose the conjuncture of women’s social status at the time of their production, rethinking – through female figures – myths, beliefs and stereotypes linked to women.